Involvement and Decisions of Young Professionals on Stock Investments - Medalla, Mark Noel; Nacua, Via Blanca; Tabuelog, Emilie Joy; Jortil, Mariza; Niere, Marvin Ian; Macaurao, Hafsah; Sejuela, Jasmine; Gaviola, Shyra Mae; Gonzales, Shan Chaira; Jumao-as, Reina Richa; Guy, Gwyndharell (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Young professionals in the Philippines show low stock market involvement due to behavioral biases, poor risk assessments, lack of confidence to invest, and limited understanding or trust in digital investment tools. This study examined the influence of determinants of stock market involvement to stock investment decisions among 385 young professionals in Cebu City aged 20-35, a demographic with growing financial capacity but limited involvement, while also accounting the impact of demographic factors. Employing descriptive statistics, Pearson Correlation Coefficient, and Chi-Square Tests, results revealed that age, monthly income, and years of stock investment experience significantly affect involvement and investment decisions. Strong correlations were found between stock market awareness and investment behaviors, risk perception, and technology adoption with key investment decision factors, including consideration of economic conditions (r=.696), technical indicators (r=.620), market volatility (r=.684), and stock market indices (r=.606). Results affirm the Theory of Planned Behavior, Prospect Theory, and the Technology Acceptance Model, while supporting the hypothesis that a significant relationship exists between the levels of involvement and investment decisions. The findings underscore the importance of personalized financial education, improved digital literacy, and greater regulatory transparency to foster confident, data-driven investment decisions. These insights also provide a valuable basis for financial institutions, policymakers, and fintech developers to collaboratively design accessible, behavior-sensitive, and tech-enabled programs that encourage deeper and smarter engagement in the stock market.